2011
DOI: 10.1111/j.1365-2842.2011.02272.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complete denture wearing on deglutition time: a cine‐magnetic resonance imaging study

Abstract: Purpose of the study was to evaluate the effect of complete denture wearing on deglutition time (DT), hyoid bone and larynx movements in edentulous patients with real-time balanced turbo field echo cine-magnetic resonance imaging. Subjects were examined by cine-magnetic resonance imaging in supine position during swallowing water. Two sets of images for 23 edentulous (with/without wearing complete dentures) and one for 23 dentulous patients were obtained. Radiographic outputs representing three consecutive deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…When dentures are removed, the tip of the tongue protrudes and thus the upward movements of the hyoid and the anterior movements of the larynx occur more easily then when dentures were worn [17], and as a result of this change, the opening of the upper esophageal sphincter increases and swallowing duration shortened [18]. Decreases in swallowing durations of edentulous patients were observed when dentures were removed compared to when dentures were worn [19]. Declines in sensation of oral cavity due to denture wearing, instability due to improper denture wearing or changes in tongue movements caused delays in OTTs.…”
Section: Discussionmentioning
confidence: 99%
“…When dentures are removed, the tip of the tongue protrudes and thus the upward movements of the hyoid and the anterior movements of the larynx occur more easily then when dentures were worn [17], and as a result of this change, the opening of the upper esophageal sphincter increases and swallowing duration shortened [18]. Decreases in swallowing durations of edentulous patients were observed when dentures were removed compared to when dentures were worn [19]. Declines in sensation of oral cavity due to denture wearing, instability due to improper denture wearing or changes in tongue movements caused delays in OTTs.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies [34–36••, 3840] have suggested that denture wearing had positive effects on swallowing function, conversely, one study [41] indicated that denture wearing may have negative effects on swallowing function, especially the oral transit time (OTT) and oropharyngeal swallow efficiency (OPSE). OTT is the time from the moment at which the major bolus in the oral cavity begins to move rearwards to the moment at which the front end of the bolus arrives at the point of crossing between the lower edge of mandibular ramus and the tongue base.…”
Section: Effect Of Tooth Loss and Denture Wearing On Swallowing Problemsmentioning
confidence: 99%
“…The upper and lower dental arches and jawbone were thus missing, so it was difficult for the tongue to control the bolus without dentures in the oral cavity, 24 suggesting poor bolus formation and transportation during feeding. Yamamoto et al 12 also reported that the bolus was scattered in the oral cavity and pharynx, and the scattered pieces of the bolus thus reached the hypopharynx before swallowing occurred.…”
Section: Accepted Article Accepted Articlementioning
confidence: 95%
“…Furthermore, a physiological study revealed that the use of complete dentures has beneficial effects on swallowing. Wearing dentures could decrease the risk of laryngeal penetration (8), stabilise swallowing movements (9), stabilise tongue-palate contact (10), shorten or lengthen bolus transit (11,12) and improve bolus transport dynamics (13). However, most of previous studies focused on liquid swallowing, and there were few studies focused on swallowing during feeding and swallowing of solid food.…”
Section: Introductionmentioning
confidence: 99%